Building Consensus about the Functional Vision Assessment Process: A Delphi Study. (November 2020) - Kaiser, Justin T.; Rosenblum, L. Penny; Herzberg, Tina S.
Introduction: Within the field of visual impairment, there is no set of standards that guide teachers of students with visual impairments as they conduct, report, and share functional vision assessment (FVA) results with other educational team members, and university instructors vary in how they teach the assessment process to preservice teachers. Methods: In parallel, a group of teachers of students with visual impairments and a group of university instructors completed three rounds of a Delphi study. After providing background information in Round 1, they rated 84 statements about the FVA process. The level for consensus was set at 80%. Results: Of the 84 statements, consensus was reached for 45 statements regarding the level of importance by both groups. Participants rated 11 of 22 visual skills (e.g., near acuity, distance acuity) as extremely important to include in the FVA process. Discussion: There continues to be a need to build consensus on when FVAs should be conducted, what visual skills should be included when conducting them, what should be included in reports, and with whom assessment information should be shared. The importance of conducting such assessments for all students, including students under the age of 5 years and those with additional disabilities, needs to be recognized by the field of visual impairment. Implications for practitioners: University personnel need to work together to develop consistent curricula that focuses on the FVA process. Future studies that examine the FVA practices of individual teachers are necessary.